2019
DOI: 10.1021/acsami.8b22678
|View full text |Cite
|
Sign up to set email alerts
|

Highly Uniform Synthesis of Selenium Nanoparticles with EGFR Targeting and Tumor Microenvironment-Responsive Ability for Simultaneous Diagnosis and Therapy of Nasopharyngeal Carcinoma

Abstract: Rational design of multifunctional and smart drug-delivered nanoplatforms is a promising strategy to achieve simultaneous diagnosis, real-time monitoring, and therapy of cancers. Herein, highly uniform and stable selenium nanoparticles with epidermal growth factor receptor (EGFR) targeting and tumor microenvironment-responsive ability (Se-5Fu-Gd-P(Cet/YI-12)) were designed and synthesized by using EGFR as the targeting molecule, gadolinium chelate as the magnetic resonance imaging contrast agent, 5-fluorouraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Osmotic and Inhibitory Effect for A375 Multicellular Tumor Spheroids A375 multicellular tumor spheroids (MCTS), cultured in 6-well plates for 7 days, were treated with GTe/GTe-RGD at a final concentration of 1.25 mg/L and then irradiated with X-rays at a density of 4 Gy for 3 days of observation. 65,66 The length and width of MCTS were measured and recorded every day by fluorescence microscopy. Meanwhile, a confocal laser 895 scanning microscope (Zeiss LSM, Germany) was used to detect the tumor-penetrating abilities of GTe, GTe-RGD, and RGD peptide blocked GTe-RGD.…”
Section: Cellular Uptake and Trafficking Of Gte And Gte-rgdmentioning
confidence: 99%
“…Osmotic and Inhibitory Effect for A375 Multicellular Tumor Spheroids A375 multicellular tumor spheroids (MCTS), cultured in 6-well plates for 7 days, were treated with GTe/GTe-RGD at a final concentration of 1.25 mg/L and then irradiated with X-rays at a density of 4 Gy for 3 days of observation. 65,66 The length and width of MCTS were measured and recorded every day by fluorescence microscopy. Meanwhile, a confocal laser 895 scanning microscope (Zeiss LSM, Germany) was used to detect the tumor-penetrating abilities of GTe, GTe-RGD, and RGD peptide blocked GTe-RGD.…”
Section: Cellular Uptake and Trafficking Of Gte And Gte-rgdmentioning
confidence: 99%
“…Besides, functionalized nanoSe may also be developed to improve their efficiency in combating SARS-CoV-2 [42] . NanoSe has also been found to have good biocompatibility [42] , [43] , [44] , [45] , and can also be used as an antiviral drug carrier. Therefore, considering these merits of nanoSe, it is promising in combating COVID-19.…”
Section: Using Nano-selenium To Fight Against Covid-19?mentioning
confidence: 99%
“…Se‐containing materials are widely researched as pharmaceutics because of their supposedly low toxicity and excellent biocompatibility . In the past decades, a great number of studies demonstrated that Se species are promising agents for cancer therapeutics, due to their capability of generating reactive oxygen species (ROS), which can induce apoptosis in tumor cells . Interestingly, Se‐containing compounds combined with radiotherapy appeared to specifically enhance the radiosensitivity of cancer cells resulting in a wave of selenium related publications .…”
Section: Enhancing the Effect Of Ionizing Radiationmentioning
confidence: 99%
“…past decades, a great number of studies demonstrated that Se species are promising agents for cancer therapeutics, due to their capability of generating reactive oxygen species (ROS), which can induce apoptosis in tumor cells. [88,89] Interestingly, Secontaining compounds combined with radiotherapy appeared to specifically enhance the radiosensitivity of cancer cells resulting in a wave of selenium related publications. [90][91][92] It needs to be mentioned that the mechanism of action of selenium is still not well-understood.…”
Section: Selenium Nanocarriersmentioning
confidence: 99%